(untitled) (Revista CICSA online, serie nouă/ CICSA Journal online, New Series, 2025)
The present study analyses the description of women’s clothing depicted on Trajan’s monuments of propaganda (the Column of his Forum in Rome and the Tropaeum Traian, at Adamclisi, Romania) as interpreted over time by Romanian historians and ethnologists, highlighting the often overreaching use of these monuments as evidence for the continuity of Romanian habitation on north of the Danube. The critical and comparative analysis of these perspectives offered by certain Romanian researches seeks to emphasize the ideological influence that shaped the academic writing during the communist era.